Functional anisotropic panglial networks in the lateral superior olive. Issue 11 (26th July 2016) - Augustin, Vanessa; Bold, Charlotte; Wadle, Simon L.; Langer, Julia; Jabs, Ronald; Philippot, Camille; Weingarten, Dennis J.; Rose, Christine R.; Steinhäuser, Christian; Stephan, Jonathan
Abstract : Astrocytes form large gap junctional networks that contribute to ion and neurotransmitter homeostasis. Astrocytes concentrate in the lateral superior olive (LSO), a prominent auditory brainstem center. Compared to the LSO, astrocyte density is lower in the region dorsal to the LSO (dLSO) and in the internuclear space between the LSO, the superior paraolivary nucleus (SPN). We questioned whether astrocyte networks exhibit certain properties that reflect the precise neuronal arrangement. Employing whole‐cell patch‐clamp and concomitant injection of a gap junction‐permeable tracer, we analyzed size and orientation of astrocyte networks in LSO, dLSO, and SPN‐LSO in acute brainstem slices of mice at postnatal days 10–20. The majority of LSO networks exhibited an oval topography oriented orthogonally to the tonotopic axis, whereas dLSO networks showed no preferred orientation. This correlated with the overall astrocyte morphology in both regions, i.e. LSO astrocyte processes were oriented mainly orthogonally to the tonotopic axis. To assess the spread of small ions within LSO networks, we analyzed the diffusion of Na + signals between cells using Na + imaging. We found that Na + not only diffused between SR101 + astrocytes, but also from astrocytes into SR101 − cells. Using PLP‐GFP mice for tracing, we could show that LSO networks contained astrocytes and oligodendrocytes. Together, our results demonstrate that LSO astrocytes and LSO oligodendrocytes form functional anisotropic panglial networks that are oriented predominantly orthogonally to the tonotopic axis. Thus, our results point toward an anisotropic ion and metabolite diffusion and a limited glial crosstalk between neighboring isofrequency bands in the LSO. GLIA 2016;64:1892–1911 Main Points: Lateral superior olive networks are anisotropic and oriented orthogonal to the tonotopic axis. Networks contained astrocytes and oligodendrocytes. Network anisotropy limits presumably glial crosstalk between neighboring isofrequency bands.